OPTIMALISASI MSDM SEBAGAI PENENTU KEBERHASILAN PENGELOLAAN LEMBAGA BAHASA DALAM PEMBINAAN KEAHLIAN BAHASA JEPANG DI LKP AKENO GAKUEN INDONESIA - Abdul Mu'in; Enik Rahayu (LPSDI Bina Patria, 2025)
Non-formal education through training and course institutions (LKP) plays a strategic role in equipping young generations with skills that meet global labor market demands. One of the most promising fields is foreign language learning, particularly Japanese, considering the growing cooperation between Indonesia and Japan in education, industry, and employment. This study focuses on the optimization of human resource management (HRM) as a key determinant of the success of LKP Akeno Gakuen Indonesia in developing Japanese language proficiency, especially in addressing the characteristics of Generation Z who tend to be less resilient, risk-averse, and demand interactive, technology-based learning methods. This research employed a qualitative approach using interviews, observations, and documentation. The findings indicate that HRM optimization through competency-based recruitment, instructor training, and digital learning innovation significantly improves students’ motivation, discipline, and satisfaction. Attendance increased from 70% to 85%, learning motivation from a score of 60 to 82, and student satisfaction from 62% to 78%. These results highlight that adaptive HRM is the key to the successful management of language institutions in responding to the challenges posed by Generation Z learners.